2009
DOI: 10.1017/s0022112009006375
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of formation of multiple zonal jets in the oceans

Abstract: Multiple alternating zonal jets observed in the ocean are studied with an idealized quasigeostrophic model of flow in a zonal channel. The jets are maintained by the eddies generated by the imposed, supercritical background flow. The formation, nonlinear dynamics and equilibration of the jets are explained in terms of linear stability arguments and nonlinear self-interactions of the linear eigenmodes. In the proposed mechanism, energy of the background flow is released to the primary instability mode with long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 57 publications
3
62
1
Order By: Relevance
“…These observations are in accord with the theoretical/ numerical results where primary baroclinic instability is in the form of so-called noodles [Berloff et al, 2009b].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These observations are in accord with the theoretical/ numerical results where primary baroclinic instability is in the form of so-called noodles [Berloff et al, 2009b].…”
Section: Discussionsupporting
confidence: 90%
“…Observations show that multiple zonal jets are indeed created in these regions and are quite prominent there [Maximenko et al, 2005[Maximenko et al, , 2008Sokolov and Rintoul, 2007;Thompson, 2008]. Berloff et al [2009aBerloff et al [ , 2009b suggested yet another way which leads to creation of zonal jets. The authors studied a quasigeostrophic model of flow in a zonal channel.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We term this hypothesis the "vortex-propagation mechanism". Other formation mechanisms include, but are not limited to, stationary Rossby waves (Maximenko et al, 2008), beta plumes (Afanasyev et al, 2011), radiating instabilities of the eastern boundary current (Hristova et al, 2008;Wang et al, 2012), and the nonlinear self-interactions of the linear eigenmodes (Berloff, 2005;Berloff et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Alternative hypotheses based on three-dimensional models have been proposed to explain mechanisms of QZJ generation; see Hristova et al (2008), Berloff et al (2009Berloff et al ( , 2011, Tanaka and Akitomo (2010), Wang et al (2012) and Qiu at al. (2013), among others.…”
Section: Introductionmentioning
confidence: 99%